An Empirical Research on Study Success in Times of COVID-19 Pandemic – a Case Study - Voigt, Christin; Kötter, Jonas; Kukharenka, Natallia (Complex Systems Informatics and Modeling Quarterly, 2021)
The COVID-19 pandemic and measures to contain it pushed many universities to switch to online learning in the spring of 2020. The changes took place very quickly and it became clear that the long-term consequences of such a transformation are uncertain and require more detailed study. This research attempts to analyze the impact of online learning on study success. This research makes use of triangulation with quantitative and qualitative methods. Quantitatively, it contains a path diagram with various factors that have an impact on the study success at a German university, which is based on a quantitative online survey with 1.529 participants. Qualitatively, 49 interviews were analyzed in order to identify reasons for the risk of failing to achieve study success. The relevance of technology becomes evident in the quantitative analysis, as it manifests itself in almost all categories that affect study success. Moreover, a new influencing factor appeared, the “adaption to digital teaching”, which was often considered important qualitatively.